Modelling Elastic Media with the Wavelet Transform - Rosa, Joao W. C.; Cardoso, Fabbryccio A. C. M.; Aki, Keiiti; Malvar, Henrique S.; Artola, Fredy A. V.; Rosa, Jose W. C. (Geophysical Journal International, 2001)
We present a new method for modelling 2-D elastic media with the application of the wavelet transform, which is also extended to cases where discontinuities simulate geological faults between two different elastic media. The basic method consists of the discretization of the polynomial expansion for the boundary conditions of the 2-D problem involving the stress and strain relations for the media. This parametrization leads to a system of linear equations that should be solved for the determination of the expansion coefficients, which are the model parameters, and their determination leads to the solution of the problem. The wavelet transform is applied with two main objectives, namely to decrease the error related to the truncation of the polynomial expansion and to make the system of linear equations more compact for computation. This is possible due to the properties of this finite length transform. The method proposed here was tested for six different cases for which the analytical solutions are known. In all tests considered, we obtained very good matches with the corresponding known analytical solutions, which validate the theoretical and computational parts of the project. We hope that the new method is useful for modelling real media.